Empowering Engineering Education: The Evolution and Impact of the EPICS Program in India - Naik, Santosh Madeva; Bandi, Surendra; Reddy, Lokeshwara (Journal of Engineering Education Transformations, 2025)
This paper chronicles the implementation of the Engineering Project in Community Service (EPICS) course within a curriculum, highlighting its journey of evolution from a Non Mandatory Course – Mandatory Course – Credit course for engineering students. The EPICS program was introduced in 2016 by one of the affiliated colleges in India, started this initiative to overcome employability issues, and for developing leadership skills, team work, problem solving skills in students. The goal was to inspire students to actively engage in real-time, community-oriented projects, shifting their focus from theoretical concepts to practical application. This change aimed at addressing employability concerns in India by fostering a more hands-on and service-oriented approach to engineering education. Studies the implementation of EPICS in engineering education effectively to address employability issues in India while enhancing students' technology-based learning and other skills, analyses academic performance of student whether increased after introducing the EPICS program? The EPICS program follows a comprehensive Design Thinking process, which involves identifying real-time problems, developing ideas, generating creative solutions, prototyping, designing, seeking feedback, and ultimately delivering and maintaining the outcomes. As of now, the program has successfully completed its eighth iteration. In the first iteration, EPICS was introduced as a non-mandatory course, offering an opportunity for interested students from various disciplines to participate by registering in the course voluntarily. The EPICS program, spanning four years of engineering education, has yielded positive outcomes for its students. An analysis of the program's impact reveals that 60% of students secured placements in reputed companies, 35% pursued higher studies, and 5% ventured into their own startups. Throughout the iterations, the program has actively collected reflections from students and alumni, as well as valuable feedback from parents and industry experts. Based on the insights gathered, the course structure and delivery have undergone significant changes from the initial iteration to the current one. These refinements aim at enhancing the effectiveness of the program, ensuring a more enriching and impactful learning experience for the participating students.